Can gold effectively hedge risks of exchange rate? - Wang, Kuan-Min (Journal of Business Economics and Management, 2013)
This study tests whether gold can effectively hedge exchange rate risks. We take into account the asymmetric characteristic of exchange rate fluctuations and use the dynamic panel threshold model in order to select gold prices in major gold-related currencies in the world: the Australian dollar, the Canadian dollar, the euro, the Indian rupee, the Japanese yen, the South African rand, and the British pound. Using monthly data from January 1999 to January 2010, with lagged one-period exchange rate returns (US dollar depreciation rate) as the threshold variable, the estimation results suggest that there are two thresholds at –7.5% and –3.7%. These can be divided into regime 1 (exchange rate returns ≤ –7.5%), regime 2 (–7.5% < exchange rate returns ≤ –3.7%), and regime 3 (exchange rate returns > –3.7%). Regarding the effectiveness of gold hedging, regime 2 is higher than is regime 3. The risk hedging effect of regime 1 is not significant because it might be caused by the excessive devaluation of the US dollar in the short-term and the overshooting of the exchange rate adjustment, making gold unable to hedge the devaluation risks of the US dollar.